Development of peak performance in track cycling - Schumacher, Y. O.; Müller, P.; Keul, J. (The Journal of Sports Medicine and Physical Fitness, 2001)
Retrospective analysis of peak performances can be a usefull tool for the estimation of future trends in high performance sports. The purpose of this study was to investigate the evolution of performance in track cycling from 1979 to 1999 and to asses age- and gender-related differences. METHODS: We studied the results of the world track cycling championships for this period in 200 m, 1000 m, individual and team pursuit races for elite and junior athletes. Overall trends, performance differences between rank 1 and 5, gender- and age-related differences were calculated. RESULTS: They show a significant (p<0.01) improvement in 1000 m, individual and team pursuit times for men and individual pursuit times for women. No significant evolution was seen in 200 m performance. In junior riders, only male athletes showed a continous, significant improvement of average race speed in individual and team pursuit over the study period. Gender difference was 11+/-1.8% in all disciplines at all ages. Difference between elite and junior riders ranged between 5+/-2.1% for male and 6.1+/-2.2% for female athletes. The gap between rank 1 and 5 remained constant (2-3%) over the study period. CONCLUSIONS: A continous improvement of performance over the last 20 years is visible in track cycling endurance disciplines. New technical developments show no statistical significant impact. The performance gap between male and female athletes is constant, independant of discipline or race distance and comparable to observations in other sports. Age-related differences in performance is most visible in disciplines requiering short, high intensity power output. Based on these data, estimation of possible winning times and adaptation of training programs for future track cycling competitions might be facilitated.